PhaSeDis: A Manually Curated Database of Phase Separation–disease Associations and Corresponding Small Molecules - Chen (陈韬宇), Taoyu; Tang (唐果菓), Guoguo; Li (李天昊), Tianhao; Yanghong (杨宏芷宁), Zhining; Hou (侯超), Chao; Du (杜泽州), Zezhou; You (游铠强), Kaiqiang; Ma (马利伟), Liwei; Li (李婷婷), Tingting (Genomics, proteomics & bioinformatics, 2025)
Biomacromolecules form membraneless organelles through liquid–liquid phase separation in order to regulate the efficiency of particular biochemical reactions. Dysregulation of phase separation might result in pathological condensation or sequestration of biomolecules, leading to diseases. Thus, phase separation and phase separating factors may serve as drug targets for disease treatment. Nevertheless, such associations have not yet been integrated into phase separation-related databases. Therefore, based on MloDisDB, a database for membraneless organelle factor–disease associations previously developed by our lab, we constructed PhaSeDis, the phase separation–disease association database. We increased the number of phase separation entries from 52 to 185, and supplemented the evidence provided by the original articles verifying the phase separation nature of the factors. Moreover, we included the information of interacting small molecules with low-throughput or high-throughput evidence that might serve as potential drugs for phase separation entries. PhaSeDis strives to offer comprehensive descriptions of each entry, elucidating how phase separating factors induce pathological conditions via phase separation and the mechanisms by which small molecules intervene. We believe that PhaSeDis would be very important in the application of phase separation regulation in treating related diseases. PhaSeDis is available at http://mlodis.phasep.pro.